The Influence of Intrinsic Motivation, Adoption of AI in Learning and Self-Efficacy on Academic Achievement - Citra Siwi Hanayanti; Mozart Malik Ibrahim; Lazuardy Alief; Anugriaty Indah Asmarany; Rinovian Rais; Heppi Syofya (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyse the influence of intrinsic motivation, adoption of artificial intelligence (AI) in learning, and self-efficacy on the academic achievement of high school students. More understanding is needed regarding the psychological and technological aspects that affect students' ability to learn, along with the digital revolution that is currently taking place in education. Analysis of 100 high school student respondents who completed a survey became the basis for this quantitative study. Multiple linear regression methods were used to analyse data collected through questionnaires that had been tested for validity and reliability. This study shows that students' academic achievement is positively influenced by intrinsic motivation. Students who use AI technologies such as virtual tutors and adaptive learning applications have better academic results than those who do not. This is one of the positive outcomes of integrating AI into the learning process. Self-efficacy, a mediating variable, strengthens the relationship between intrinsic motivation and academic achievement. This highlights the importance of self-belief in supporting the effectiveness of learning driven by internal motivation. These findings emphasise the importance of developing learning strategies that arouse students' intrinsic motivation, strengthen self-efficacy, and encourage optimal utilisation of AI technology. The implications of this study provide recommendations for schools, educators, and policymakers to integrate innovative approaches that support technology adaptation and student psychological strengthening to improve academic achievement in the digital era.